Researching about us without us: exploring research participation and the politics of disability rights in the context of the Mental Capacity Act 2005. Issue 6 (3rd March 2018) - Loomes, Gillian
Abstract : The right to active participation by disabled people in academic research has been discussed at length in recent years, along with the potential for such research to function as a tool in challenging oppression and pursuing disability rights. Significant ethical, legal and methodological dilemmas arise, however, in circumstances where a disabled person loses the capacity to provide informed consent to such participation. In this article, I consider disability politics and academic research in the context of the Mental Capacity Act (MCA) 2005, which sets out in Anglo-Welsh law the circumstances and requirements for research participation by individuals lacking the capacity to provide informed consent. Drawing on my own perspective on research participation in relation to physical and psychosocial disability, I consider the implications of my potential future loss of capacity (eg, if I were to be in a vegetative or minimally conscious state following an accident) for my right to participate in disability-related research. I examine the barriers to such participation and suggest that partial solutions may be found in the advance decision-making and advance care-planning frameworks of the MCA 2005 and related policy, but that current legislative and policy frameworks nevertheless still curtail my rights with regard to research participation on loss of capacity to consent. In so doing, I seek to provoke debate concerning what this legislative provision means for the disability rights movement, and the possibilities and challenges it presents to the movement's commitment to 'nothing about us without us'.